O’RTA MAKTABLARDA XORIJIY MATN USTIDA ISHLASH ORQALI O’QISHNI O’RGATISH («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article talks about teaching high school students to read, correctly understand foreign language texts, and creative thinking by working on the text.
Keywords: text, complex texts, respective speech, reproductive speech, work on the text, language material.